2021
DOI: 10.1097/cad.0000000000001102
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of low-dose Apatinib in the management of stage IV luminal-type breast cancer: a case report and literature review

Abstract: Advanced breast cancer (ABC) is incurable. Previous studies have shown that vascular endothelial growth factor (VEGF) inhibitors play a significant role in the angiogenesis of breast carcinoma. Apatinib, a highly selective orally administered small-molecule tyrosine kinase inhibitor that targets vascular endothelial growth factor receptor-2 (VEGFR2) has successfully been used as a second- and third-line agent in the management of ABC. There are also multiple reported cases where Apatinib was miraculously effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Due to the high malignancy of gallbladder cancer, chemotherapy can directly kill tumor cells [ 6 , 7 ]. Gemcitabine, oxaliplatin, and apatinib all have significant effects on the treatment of tumors [ 8 , 9 ]. Gemcitabine has a strong broad-spectrum antitumor activity and a unique mechanism of action and is widely used in the treatment of malignant tumors in clinical practice; oxaliplatin has the advantage of significant effects and few adverse effects; and apatinib is able to antagonize vascular endothelial growth factor receptor 2 (VEGFR-2) and can effectively promote apoptosis of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high malignancy of gallbladder cancer, chemotherapy can directly kill tumor cells [ 6 , 7 ]. Gemcitabine, oxaliplatin, and apatinib all have significant effects on the treatment of tumors [ 8 , 9 ]. Gemcitabine has a strong broad-spectrum antitumor activity and a unique mechanism of action and is widely used in the treatment of malignant tumors in clinical practice; oxaliplatin has the advantage of significant effects and few adverse effects; and apatinib is able to antagonize vascular endothelial growth factor receptor 2 (VEGFR-2) and can effectively promote apoptosis of tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the antitumor activity of apatinib in several solid tumors (Zhang et al, 2022b;Xiang et al, 2022;Zhu et al, 2022). Tumor angiogenesis plays an important role in tumor development and metastasis, and antiangiogenic drugs may improve the efficacy of conventional chemotherapy in the treatment of breast cancer (Liu et al, 2021;Lv et al, 2021). Apatinib inactivates the NF-κB signaling pathway, which makes TNBC cells sensitive to anthracyclines in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it has been reported that apatinib could be an effective option for the HER2-positive tumors. Luckily, a female patient with HR-positive and HER2-negative stage of breast cancer showed significant improvement in the symptoms upon low dose of apatinib [ 20 ]. However, the details about other additional treatments or clinical history were not provided; hence, efficacy of the apatinib in this case is doubtful.…”
Section: Discussionmentioning
confidence: 99%